Discussion of Financial Integration at the Global Market Era - TURSOY, Turgut; BERK, Niyazi (Journal of Advanced Studies in Finance, 2020)
This paper purpose is to discuss the latest troubling episode and remind the most critical event again at the world is the integration. First, the last attempt by the countries had been discussing and pronoun that the free market and its extensions are the most prominent phenomena around the world that market participants' perceptions are determined the equilibria prices freely. All the development into the markets witnesses that free market dynamics and the creation of the single global market is the most dominant factor to create a tremendous stimulus behind economic growth. This paper consequently supporting the view that financial integration is providing the necessary conditions to risk-sharing and capital flows to stimulus the economic growth with the expected level at global.